2022
DOI: 10.1155/2022/2475169
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α Promotes BMP9-Mediated Osteoblastic Differentiation and Vascularization by Interacting with CBFA1

Abstract: Bone morphogenetic protein 9 (BMP9) as the most potent osteogenic molecule which initiates the differentiation of stem cells into the osteoblast lineage and regulates angiogenesis, remains unclear how BMP9-regulated angiogenic signaling is coupled to the osteogenic pathway. Hypoxia-inducible factor 1α (HIF1α) is critical for vascularization and osteogenic differentiation and the CBFA1, known as runt-related transcription factor 2 (Runx2) which plays a regulatory role in osteogenesis. This study investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
2
0
4
Order By: Relevance
“…BMP-9 increases the HIF-1α expression, and the downregulation of HIF-1α inhibits osteoblast differentiation induced by BMP-9, a mechanism that is regulated by Runx2, a downstream target of HIF-1α [ 27 , 28 , 33 ]. Based on this cellular mechanism, we worked with MSCs +BMP-9 , an immortalized cell line that expresses BMP-9, which enhances their ability to induce bone repair [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP-9 increases the HIF-1α expression, and the downregulation of HIF-1α inhibits osteoblast differentiation induced by BMP-9, a mechanism that is regulated by Runx2, a downstream target of HIF-1α [ 27 , 28 , 33 ]. Based on this cellular mechanism, we worked with MSCs +BMP-9 , an immortalized cell line that expresses BMP-9, which enhances their ability to induce bone repair [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BMP-9 increased the HIF-1α protein expression and the inactivation of HIF-1α with either a chemical inhibitor or siRNA reduced the extracellular matrix mineralization induced by BMP-9 in cultures of osteoblasts, indicating that HIF-1α plays an essential role in the BMP-9-mediated osteoblast differentiation [ 27 ]. Chromatin immunoprecipitation assays in immortalized mouse embryonic fibroblasts showed that the runt-related transcription factor 2 (Runx2) is a downstream target of HIF-1α that regulates osteoblast differentiation induced by BMP-9 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A modificação gênica de MSCs para expressar BMP-9, a mais osteogênica da família das BMPs, induz aumento da formação óssea, mas ainda sem resultar na regeneração do tecido ósseo (CHENG et al, 2003;FREITAS et al, 2021), indicando a necessidade de outras modificações dessas MSCs para aumentar sua efetividade terapêutica. Nesse sentido, as evidências de que BMP-9 e HIF-1α, que está aumentado em condições de Hipóxia celular, têm efeito sinérgico sobre MSCs para aumentar seu potencial angiogênico e osteogênico (AMIR et al, 2022;HU et al, 2013;LI et al, 2022) sugerem que MSCs BMP-9+ submetidas à Hipóxia são promissoras para se obter a regeneração do tecido ósseo. Neste estudo, foram avaliados in vitro os efeitos da Hipóxia sobre as vias de sinalização de BMPs em MSCs BMP-9+ e o efeito do secretoma de MSCs BMP-9+ submetidas à Hipóxia sobre a proliferação, migração e diferenciação osteoblástica de MSCs e osteoblastos por serem essas células aquelas mais envolvidas na regeneração do tecido ósseo.…”
Section: Discussionunclassified
“…Considerando que há sinergismo entre os efeitos da BMP-9 e de HIF-1 na diferenciação osteoblástica de MSCs, mas observados em experimentos com adição exógena de BMP-9 (AMIR et al, 2022;HU et al, 2013;LI et al, 2022), neste estudo investigamos o efeito da Hipóxia na expressão proteica de BMP-9 e na expressão de genes envolvidos na sinalização de BMPs em MSCs BMP-9+ . Interessante que a BMP-9 aumenta a expressão de HIF-1 (AMIR et al, 2022;HU et al, 2013;LI et al, 2022), mas esse não afeta a expressão proteica de BMP-9, mas atua sobre a via de sinalização de BMPs aumentando a expressão gênica de Bmp-2, do receptor Bmpr1a, da Smad1 e do fator de transcrição Hey-1.…”
Section: Discussionunclassified
See 1 more Smart Citation